PROBLEMS AND PROSPECTS FOR THE DEVELOPMENT OF RURAL TOURISM IN THE VOLOGDA REGION - M. V. Andreeva; I. V. Kryukova (Вестник университета)
The paper considers scientific approaches to determining the essence of rural tourism and agrotourism. The authors conduct a review of the current state and trends in the development of tourism, including rural tourism, in the Vologda region. The article characterizes the activities of the government bodies of the Vologda region to create conditions for the development of the tourism industry. The study proves the prospects for the development of rural tourism in the region, shows the possibilities of forming complex tourist products. The article identifies the main problems of rural tourism development in the region and determines the directions of their solution. The  paper considers the role of local governments in the development of rural tourism. The authors justify the necessity of more active implementation of the project approach in the practice of municipal administration in order to fully apply the tourist potential of the region’s territories. The study emphasizes public-private and municipal-private partnerships as one of the most effective ways to attract investment in the development of  tourist infrastructure.